Correlation between Biofilm Development and Antibiotic Resistance in Staphylococcus haemolyticus - Yaser Mohammedali; Suha Abed (Medicinski glasnik, 2025)
Aim: This study aimed to evaluate antibiotic resistance, biofilm formation, and the presence of virulence-associated genes in Staphylococcus haemolyticus isolates. Methods: Clinical specimens were obtained from patients in Mosul city. Antibiotic susceptibility was determined using the Kirby-Bauer disk diffusion method against fourteen antibiotics Biofilm production was assessed by both the tube adherence method and the microtiter plate assay. Polymerase chain reaction (PCR) was employed to detect selected resistance and virulence genes. Results: The isolates exhibited high resistance rates to ampicillin (94.7%) and cloxacillin (94.7%). These antibiotics were tested separately to compare ?-lactamase-labile (ampicillin) and ?-lactamase-stable (cloxacillin) penicillins. All isolates were uniformly susceptible to vancomycin. Nitrofurantoin was not included in the final interpretation due to its limited clinical relevance in non-urinary tract infections, especially considering that S. haemolyticus is not a typical uropathogen. Variable resistance patterns were observed with other antibiotics. All isolates demonstrated biofilm production. PCR analysis revealed the presence of the SH gene in 100% of isolates. The mecA gene, conferring methicillin resistance, was detected in 88.88% of isolates; tetK (tetracycline resistance) in 83.33%; and ermC (erythromycin resistance) in 26.31%. Among the virulence factors, hla and fnbB were found in 100% and 73.68% of isolates, respectively. Conclusion: The study highlights the alarming antibiotic resistance, strong biofilm-forming ability, and high prevalence of virulence and resistance genes in S. haemolyticus, reinforcing concerns over the global spread of multidrug-resistant organisms.
Keywords: Antibiotic; biofilm; Staphylococcus haemolyticus; Virulence factors.